Safety and effectiveness of response‐guided therapy using pegylated interferon and ribavirin for chronic hepatitis C virus infection in patients on maintenance dialysis. Issue 9 (9th August 2017) - Goel, Amit; Bhadauria, Dharmendra Singh; Kaul, Anupma; Prasad, Narayan; Gupta, Amit; Sharma, Raj Kumar; Rai, Praveer; Aggarwal, Rakesh
Abstract: Aim: Treatment of hepatitis C virus (HCV) infection in patients with end‐stage renal disease (ESRD) is difficult. Addition of ribavirin to pegylated‐interferon (Peg‐IFN) may help to improve the treatment response. Further, treatment duration could be shortened using a response‐guided treatment (RGT) approach. Methods: We retrospectively reviewed records of treatment‐naïve adult patients with ESRD and chronic HCV infection who had been treated with Peg‐IFN and low‐dose ribavirin using a RGT approach. Rapid responders (undetectable HCV‐RNA at 4 weeks) received treatment for 12 weeks, and slow responders (HCV‐RNA detectable at 4 weeks, but undetectable or with >2.0 log10 reduction at week 12) for 24 (genotype 3; GT3) or 48 (genotype 1; GT1) weeks. In those without such reduction (null responders), treatment was discontinued. Results: Of 26 non‐cirrhotic patients (GT1 15, GT3 11) treated, four (15%; GT1 3, GT3 1) were null responders. Twenty‐two (85%) patients had either rapid ( n = 14 (54%); GT1 10, GT3 4) or slow response ( n = 8 (31%); GT1 2, GT3 6). Of them, 21 patients had undetectable RNA at the end of treatment; one could not complete the treatment and was lost thereafter. There were no deaths during treatment. Three patients relapsed and three others died in 6 months after stopping treatment. Overall, 15/26 (58%) patients attained SVR24. Fourteen patients underwent transplantation beginning one month after treatment completion, and all were relapse‐free after 17 (14–24) months of follow‐up. Conclusion: RGT using Peg‐IFN and ribavirin was effective in ESRD patients on maintenance dialysis. Renal transplant was safely done within one month of completing such treatment. Summary at a Glance: Response‐guided treatment using Peg‐IFN and ribavirin was effective in ESRD patients on maintenance dialysis. Renal transplant was safely done within one month of completing such treatment.